Look‐back study on recipients of Parvovirus B19 (B19V) DNA‐positive blood components. Issue 4 (5th June 2015) - Juhl, D.; Özdemir, M.; Dreier, J.; Görg, S.; Hennig, H.
<x xml:space="preserve">Abstract</x> Background and Objectives To assess the relevance of Parvovirus B19 (B19V) DNA at low to intermediate concentrations in blood donors for the recipients of their blood components. Material and Methods We studied recipients of B19V DNA‐positive blood components [red blood cell concentrates (RBCs), pooled platelet concentrates and fresh frozen plasma]. This included archived pretransfusion samples as well as follow‐up samples investigated by ELISA or NAT and genome sequence analysis. Results In 132 out of 424 recipients, we could detect no anti‐B19V IgG before transfusion. In 67 out of 132 sero‐negative recipients, a follow‐up sample was available. Sixty‐five of these received blood components from donors with <104 IU B19V DNA/ml plasma and had no evidence of transfusion‐transmitted (TT)‐B19V infection. Homology in genome sequences in donor and recipient provided evidence for a TT‐B19V infection in two recipients. Both patients received RBC containing 3·4 × 106 and 1·8 × 104 IU B19V DNA/ml plasma, respectively. The anti‐B19V IgG titres in the donors were 2 and 76 IU/ml plasma, respectively. The antibodies in the second donor were directed against capsid proteins and are thus considered as potential neutralizing antibodies. Conclusions TT‐B19V infections through blood components with low (<104 IU/ml plasma) B19V DNA concentrations did not occur in our study. One of the TT‐B19V infections occurred from RBC with intermediate B19V DNA concentration despite the presence of potential neutralizing antibodies in the donor, but its clinical significance was low.